Performance and Maximum Functional Masticatory Force in Patients with Dentomucosal-supported and Implant-supported Removable Partial Dentures - Mauricio Toro; Alain Manuel Chaple-Gil; Fernando Romo; Leonardo Díaz (Revista Cubana de Estomatología, 2024)
Introduction: Due to edentulousness, masticatory performance and masticatory force decrease, which implies a disorganization and decompensation of the stomatognathic system with forces provoked by mastication, which are distributed in the bone through teeth and mucous membranes and cause bone resorption in edentulous areas.